Does a Reduced Number of Muscle Stem Cells Impair the Addition of Sarcomeres and Recovery from a Skeletal Muscle Contracture? A Transgenic Mouse Model. Issue 4 (April 2020) - Dayanidhi, Sudarshan; Kinney, Matthew C.; Dykstra, Peter B.; Lieber, Richard L.
Abstract: Background: Children with cerebral palsy have impaired muscle growth and muscular contractures that limit their ROM. Contractures have a decreased number of serial sarcomeres and overstretched lengths, suggesting an association with a reduced ability to add the serial sarcomeres required for normal postnatal growth. Contractures also show a markedly reduced number of satellite cells—the muscle stem cells that are indispensable for postnatal muscle growth, repair, and regeneration. The potential role of the reduced number of muscle stem cells in impaired sarcomere addition leading to contractures must be evaluated. Questions/purposes: (1) Does a reduced satellite cell number impair the addition of serial sarcomeres during recovery from an immobilization-induced contracture? (2) Is the severity of contracture due to the decreased number of serial sarcomeres or increased collagen content? Methods: The hindlimbs of satellite cell-specific Cre-inducible mice (Pax7 CreER/+ ; Rosa26 DTA/+ ; n = 10) were maintained in plantarflexion with plaster casts for 2 weeks so that the soleus was chronically shortened and the number of its serial sarcomeres was reduced by approximately 20%. Subsequently, mice were treated with either tamoxifen to reduce the number of satellite cells or a vehicle (an injection and handling control). The transgenic mouse model with satellite cell ablation combined with a casting model to reduce serial sarcomere number recreates two features observed in muscular contractures in children with cerebral palsy. After 30 days, the casts were removed, the mice ankles were in plantarflexion, and the mice's ability to recover its ankle ROM by cage remobilization for 30 days were evaluated. We quantified the number of serial sarcomeres, myofiber area, and collagen content of the soleus muscle as well as maximal ankle dorsiflexion at the end of the recovery period. Results: Mice with reduced satellite cell numbers did not regain normal ankle ROM in dorsiflexion; that is, the muscles remained in plantarflexion contracture (-16° ± 13° versus 31° ± 39° for the control group, -47 [95% confidence interval -89 to -5]; p = 0.03). Serial sarcomere number of the soleus was lower on the casted side than the contralateral side of the mice with a reduced number of satellite cells (2214 ± 333 versus 2543 ± 206, -329 [95% CI -650 to -9]; p = 0.04) but not different in the control group (2644 ± 194 versus 2729 ± 249, -85 [95% CI -406 to 236]; p = 0.97). The degree of contracture was strongly associated with the number of sarcomeres and myofiber area (r 2 =0.80; P < 0.01) rather than collagen content. No differences were seen between groups in terms of collagen content and the fraction of muscle area. Conclusions: We found that a reduced number of muscle stem cells in a transgenic mouse model impaired the muscle's ability to add sarcomeres in series and thus to recover from an immobilization-induced contracture. Clinical Relevance: The results of our study in transgenic mouse muscle suggests there may be a mechanistic relationship between a reduced number of satellite cells and a reduced number of serial sarcomeres. Contracture development, secondary to impaired sarcomere addition in muscles in children with cerebral palsy may be due to a reduced number of muscle stem cells.